Ethnobotanical Survey of the Plants Used In the Treatment of Diabets in Adilabad and Nirmal Districts of Telangana State - Ranjalkar K.M,; N. Ramakrishna, (International Journal of Scientific Research in Science and Technology, 2025)
The paper deals with the plants based folk role practices used in the treatment of diabetes. The study was conducted in two districts (Adilabad and Nirmal) of Telangana State India, and the state of Telangana a rich in floral diversity. Even though modern medical facilities are available in these Places, people in villages still are plant therapy to a considerable extent. This may be attributed to the rich floral wealth of the state, which makes the access to the medicinal plants comparatively easy, the lower cost factor, and to a popular belief that plant derived medicines are better suited for the body. The impact of modernization and preservation of these practices are essential.
Keywords: Diabetes; Folk Practices; Floral diversity; Telangana State